New Caledonian Triassic Bryozoa. (21st March 2016) - Ernst, Andrej; Schäfer, Priska; Grant-Mackie, Jack A.
Abstract: Four trepostome bryozoan species are described from the Upper Triassic of New Caledonia. They include one new genus Metastenodiscus n. gen. The studied fauna shows strong paleobiogeographic relations to New Zealand and less so to Japan. Morphological similarities between Middle Paleozoic and Triassic trepostome bryozoans (e.g., abundant diaphragms) are explained by homeomorphy.